Seasonal variation of atmospheric ozone in India and some ozone-weather relationships (MAUSAM, 1963)
An analysis is made of the total ozone amounts determined at the four regular ozone stations in India during the period 1958 to 1960. While the ozone content at Srinagar and Delhi is relatively higher during January-April, that at Kodaikanal is relatively higher during June-September. A very interesting feature of the ozone distribution in India is reversal of the latitudinal gradient of total ozone during the monsoon season which leads to higher ozone in the south than in the north. A possible mechanism to account for this reversal is suggested in terms of seasonal variations in the tropopause height. Good correlations are observed between day to day fluctuations in the ozone at Srinagar and changes in the 500 mb contour heights at Delhi caused by the movement of disturbances in the westerlies. A case study of an abnormal in increase of ozone in association with a western depression in March 1960 is also discussed. The increase of ozone is apparently caused more by vertical descent of stratospheric ozone rich air than by advection of northerly winds.